Design and Calibration of a Large Open-Ended Coaxial Probe for the Measurement of the Dielectric Properties of Concrete - Filali, B.; Boone, F.; Rhazi, J.; Ballivy, G. (IEEE transactions on microwave theory and techniques, 2008)
The subject of this paper is the design and calibration of an open-ended coaxial probe for the nondestructive measurement of the dielectric properties of concrete. Measurements are made between 100-900 MHz, frequencies which are often used in geophysics and civil engineering for ground penetrating radar inspection. The probe is calibrated using measurements on saline solutions in conjunction with three different mathematical techniques for comparative study. Measurements of mortar and concrete specimens having different water/cement ratios were made in order to observe the standard deviations due to their heterogeneous nature. Similar to the case of relatively homogeneous rock specimens (limestone and granite), the standard deviation for heterogeneous concrete samples do not exceed 5%. In addition, the effect of the concrete's porosity on its dielectric properties was clearly observed: measured permittivity between 4-4.5 at 900 MHz for porous concrete, and between 6.5-7.5 at 900 MHz for dense concrete.